2014
DOI: 10.1016/j.jpeds.2014.02.054
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Outcomes of the Surfactant Positive Pressure and Oximetry Randomized Trial (SUPPORT)

Abstract: Objective To explore the early childhood pulmonary outcomes of infants who participated in the NICHD SUPPORT Trial, using a factorial design that randomized extremely preterm infants to lower vs. higher oxygen saturation targets and delivery room CPAP vs. intubation/surfactant, found no significant difference in the primary composite outcome of death or BPD. Study design The Breathing Outcomes Study, a prospective secondary to SUPPORT, assessed respiratory morbidity at 6 month intervals from hospital dischar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(93 citation statements)
references
References 34 publications
4
88
0
1
Order By: Relevance
“…Similarly to the trial reported here, neurodevelopmental outcomes did not differ between study groups 10. Respiratory morbidities, however, were significantly reduced in the CPAP group at 18–22 months,26 which might, given the experience of earlier trials, correlate with neurodevelopmental performance at school age 27…”
Section: Discussionsupporting
confidence: 64%
“…Similarly to the trial reported here, neurodevelopmental outcomes did not differ between study groups 10. Respiratory morbidities, however, were significantly reduced in the CPAP group at 18–22 months,26 which might, given the experience of earlier trials, correlate with neurodevelopmental performance at school age 27…”
Section: Discussionsupporting
confidence: 64%
“…In addition, data supports the early use of surfactant among infants requiring mechanical ventilation, compared to delaying treatment until the severity of RDS worsens 28 . In the delivery room, studies suggest that initial CPAP, rather than intubation and surfactant, is a potentially more favorable approach to reduce long-term respiratory morbidity in EPT infants with RDS 29 and is a recommended approach in EPT infants who are spontaneously breathing in the delivery room 30 .…”
Section: Short-term Morbiditiesmentioning
confidence: 99%
“…Furthermore, in SUPPORT both those with and without BPD had ongoing respiratory morbidity at 2 years, although less respiratory morbidity in those randomized to initial CPAP versus intubation. 79 In addition, although rates of severe ROP were increased in the higher target group, severe visual impairment at 2 years was very low (for the lower and higher targets in SUPPORT 1.0% and 1.2%; in COT 1.0% and 0.6%; in BOOST-NZ 0% and 0.7%), [55][56][57] indicating that current detection and treatment of ROP in these infants was largely successful.…”
Section: What Can Be Concluded From the Evidence Published To Date?mentioning
confidence: 95%